Integrated petrophysical and microfacies analyses for a reservoir quality assessment of the Asmari Dolostone sequence in the Khesht Field, SW Iran. (January 2022) - Fallah-Bagtash, Roghayeh; Adabi, Mohammad H.; Nabawy, Bassem S.; Omidpour, Armin; Sadeghi, Abbas
Graphical abstract: Highlights: Petrographically, seven non-clastic microfacies are assigned for the Asmari fractured dolomite reservoir. Dolomitization, cementation and compaction are the main reservoir quality-reducing factors. Dissolution and reservoir fracturing are the main reservoir quality-enhancing factors. Petrophysically, the Asmari reservoir sequence is divided into five reservoir rock types and four hydraulic flow units. Abstract: The Asmari Formation is one of the most important prolific reservoirs along both sides of the Persian Gulf. The present study aims to characterize the fractured dolomite of the Asmari reservoir sequence in SW Iran. Such characterization can be achieved through a petrophysical reservoir characterization using core data integrated with a detailed microfacies analysis and a detailed study on the dominant diagenetic features. The detailed microfacies analysis indicates that the Asmari reservoir can be discriminated into seven non-clastic microfacies (laminated to massive anhydrite, sandy dolomudstone, peloidal bioclastic dolowackestone, peloidal foraminiferal dolowackestone/dolopackstone, peloidal bioclastic dolopackstone/dolograinstone, framestone, and dolograinstone microfacies). These microfacies have been primarily deposited in tidal flat, lagoonal, and carbonate shoal depositional environments. Petrophysically, some X-Y plots were established to present the available petrophysical core data (porosity ∅He, horizontal and vertical permeabilities, kH and kV, respectively) to enable a mathematical reservoir modeling. Besides, the reservoir quality has been defined using the flow zone indicator (FZI), reservoir quality index (RQI), and the effective pore radius (R35 ). Based on these petrophysical core data and quality parameters, the studied samples can be subdivided into five reservoir rock types (RRTs). Also, reservoir zonation on the borehole scale using the improved stratigraphic modified Lorenz technique (ISML) indicated that the characterized reservoir can be subdivided into four hydraulic flow units (HFU-1, HFU-2, HFU-3, and HFU-4). The HFU-2 (dolograinstone, dolopackstone, and framestone samples) is characterized by the best reservoir quality (average ∅He  = 7.8%, kH  = 95.2 md, RQI = 0.84 µm, FZI = 15.9 µm, and R35  = 10.5 µm); it is composed of RRT1 and RRT2 samples. On the other side, the lowest reservoir quality is assigned to the HFU-3 which is composed of the RRT5 (dolomudstone and evaporates, average ∅He  = 11.5%, kH  = 0.24 md, RQI = 0.04 µm, FZI = 0.22 µm, and average R35  = 0.21 µm). The prevailed reservoir characteristics of the Asmari dolostone sequence in SW Iran are mostly controlled by replacive and pervasive dolomitization, fracturing, and cementation by anhydrite.